Structure of the chorioretinal complex in the rabbit eye after vitrectomy. Report 2. Vitreous cavity irrigation with different temperature solutions for 60 minutes - O.S. Zadorozhnyy; R.E. Nazaretian; V.V. Myrnenko; V.A. Naumenko; E.V. Maltsev; N.V. Pasyechnikova; V.V. Shafranskii (Ukrainian Society of Ophthalmologists, 2018)
Background: It remains poorly understood what should be the temperature of the irrigation solution for intraocular surgery and how long it is reasonable to use irrigation solutions during vitrectomy. Purpose: To investigate the structure of rabbit chorioretinal complex after vitrectomy with the use of irrigation solutions having different temperatures for 60 minutes. Materials and Methods: Twelve Chinchilla rabbits (24 eyes) were divided into two experimental groups and one control group. The two experimental groups, each of 5 rabbits (10 eyes), underwent a three-port pars plana vitrectomy with either 22°C or 5°C irrigation solution. Two intact rabbits (4 eyes) were used as controls for comparison. The duration of irrigation/aspiration was 60 minutes. Specimens for histology were obtained at days 1 and 7 after surgery. The chorioretinal complex (i.e., the choroid and retina) was histologically examined. Results: After vitrectomy with 60-minute continuous vitreous cavity cooling with either the 22°C or 5°C irrigation solution, we found retinal structural changes in the form of uneven edema, (a) predominantly in the inner retinal layers, at day 1, and (b) in both the inner and outer retinal layers, at day 7. There were destructive changes in the inner retinal layers on some slides from rabbits of both groups. In addition, the choroid appeared somewhat thickened. Conclusion: In the rabbit eyes after vitrectomy with 60-minute continuous vitreous cavity cooling with either the 22°C or 5°C irrigation solution, we found the uneven retinal edema that is likely to be mediated by aseptic inflammatory response to cooling-induced and mechanical damage to the retina, and might be also associated with the composition of the irrigation fluid.